Family, Story, and Identity Migrant Women Living with Ambivalence - Mallman, Senem (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
How do second-generation migrant women connect with their cultural heritage when ethnic ties have been weak or absent for most of their lives? Family, Story and Identity presents the life stories of twenty women of various ethnicities, analysis of published autobiographies, as well as autoethnographic accounts of the author's experiences, to show how stories connect adult children of immigrants with their cultural heritage. The collecting of stories comes in various forms and can include brief visits to ancestral homelands, documenting family histories and genealogies, and gathering stories, folktales, and recipes. Senem Mallman found that, as adults, many children of immigrants actively seek out family histories and stories in order to connect with their cultural heritage and with their parents, and to pass this knowledge on to their own children. She argues that seeking out stories enables the second-generation to find a place within their family narrative. This pursuit of stories leads them toward developing new perspectives about their culture, family and life in Australia, and new ways of living with their cultural ambivalence.